GJB4 variants linked to skin disease exhibit a trafficking deficiency en route to gap junction formation that can be restored by co-expression of select connexins - Lucaciu, Sergiu A.; Figliuzzi, Rhett; Neumann, Ruth; Nazarali, Samina; Del Sordo, Luigi; Leighton, Stephanie E.; Hauser, Alexandra; Shao, Qing; Johnston, Danielle; Bai, Donglin; Laird, Dale W. (Frontiers in Cell and Developmental Biology, 2023)
Epidermal keratinocytes are enriched with at least nine connexins that are key regulators of epidermal homeostasis. The role of Cx30.3 in keratinocytes and epidermal health became evident when fourteen autosomal dominant mutations in the Cx30.3-encoding GJB4 gene were linked to a rare and incurable skin disorder called erythrokeratodermia variabilis et progressiva (EKVP). While these variants are linked to EKVP, they remain largely uncharacterized hindering therapeutic options. In this study, we characterize the expression and functional status of three EKVP-linked Cx30.3 mutants (G12D, T85P and F189Y) in tissue-relevant and differentiation-competent rat epidermal keratinocytes. We found that GFP-tagged Cx30.3 mutants were non-functional likely due to their impaired trafficking and primary entrapment within the endoplasmic reticulum (ER). However, all mutants failed to increase BiP/GRP78 levels suggesting they were not inducing an unfolded protein response. FLAG-tagged Cx30.3 mutants were also trafficking impaired yet occasionally exhibited some capacity to assemble into gap junctions. The pathological impact of these mutants may extend beyond their trafficking deficiencies as keratinocytes expressing FLAG-tagged Cx30.3 mutants exhibited increased propidium iodide uptake in the absence of divalent cations. Attempts to rescue the delivery of trafficking impaired GFP-tagged Cx30.3 mutants into gap junctions by chemical chaperone treatment were ineffective. However, co-expression of wild type Cx30.3 greatly enhanced the assembly of Cx30.3 mutants into gap junctions, although endogenous levels of Cx30.3 do not appear to prevent the skin pathology found in patients harboring these autosomal dominant mutations. In addition, a spectrum of connexin isoforms (Cx26, Cx30 and Cx43) exhibited the differential ability to trans-dominantly rescue the assembly of GFP-tagged Cx30.3 mutants into gap junctions suggesting a broad range of connexins found in keratinocytes may favourably interact with Cx30.3 mutants. We conclude that selective upregulation of compatible wild type connexins in keratinocytes may have potential therapeutic value in rescuing epidermal defects invoked by Cx30.3 EKVP-linked mutants.